225Ac‐labeled CD33‐targeting antibody reverses resistance to Bcl‐2 inhibitor venetoclax in acute myeloid leukemia models. (21st December 2020) - Garg, Ravendra; Allen, Kevin J. H.; Dawicki, Wojciech; Geoghegan, Eileen M.; Ludwig, Dale L.; Dadachova, Ekaterina
ABSTRACT: Purpose: Despite the availability of new drugs, many patients with acute myeloid leukemia (AML) do not achieve remission and outcomes remain poor. Venetoclax is a promising new therapy approved for use in combination with a hypomethylating agent or with low‐dose cytarabine for the treatment of newly diagnosed older AML patients or those ineligible for intensive chemotherapy. 225 Actinium‐lintuzumab ( 225 Ac‐lintuzumab) is a clinical stage radioimmunotherapy targeting CD33 that has shown evidence of single‐agent activity in relapsed/refractory AML. Increased expression of MCL‐1 is a mediator of resistance to venetoclax in cancer. Experimental design: Here we investigated the potential for 225 Ac‐lintuzumab‐directed DNA damage to suppress MCL‐1 levels as a possible mechanism of reversing resistance to venetoclax in two preclinical in vivo models of AML. Results: We demonstrated that 225 Ac‐lintuzumab in combination with venetoclax induced a synergistic increase in tumor cell killing compared to treatment with either drug alone in venetoclax‐resistant AML cell lines through both an induction of double‐stranded DNA breaks (DSBs) and depletion of MCL‐1 protein levels. Further, this combination led to significant tumor growth control and prolonged survival benefit in venetoclax‐resistant in vivo AML models. Conclusions: There results suggest that the combination of 225 Ac‐lintuzumab with venetoclax is a promising therapeutic strategy for the treatment of patients with venetoclax‐resistant AML. Clinical trial of this combination therapy (NCT03867682) is currently ongoing. Abstract : Long‐term survival of adult patients with acute myeloid leukemia (AML) remains unsatisfactory.We describe the results of a mechanistic and efficacy study combining venetoclax (ABT‐199), a recently approved BCL2 inhibitor, and the clinical stage CD33‐targeting antibody radiolabeled with 225 Actinium ( 225 Ac‐lintuzumab) in two venetoclax‐resistant AML models in vitro and in vivo. The study demonstrated dramatic synergy of these two drugs both in vitro and in vivo due to the decrease in BCL‐2 and MCL‐1 levels and induction of double DNA strand breaks. Since both venetoclax and 225 Ac‐lintuzumab are already used in patients, we anticipate that rapid translation of this combination approach into the clinic will benefit patients with AML.